2022
DOI: 10.23937/2572-3243.1510111
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Disorders among Sugar Factory Workers in Jinja-Uganda: A Cross-Sectional Study

Abstract: Introduction: Globally, musculoskeletal disorders (MSDs) combined account for more than a fifth of the total years lived with disability. This condition affects workers alone and people across the life-course in all regions of the world. Despite this long-standing awareness, MSDs continue to be the main reason associated with people with a work-related illness. The aim of this study is to explore the prevalence of work-related musculoskeletal disorders among workers in sugar factories in Jinja-Uganda. Methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…In a recent report by WHO on analysis of Global Burden of Disease (GBD) 2019, data revealed that approximately 1.71 billion people globally live with musculoskeletal disorders, which include low back pain, neck pain, amputation (Cieza et al, 2020;Babantunde et al, 2022) Furthermore, this burden of disability as provided and estimated by the above summary on measures of health has an impact on the individual's quality of life, during and outside of their job, and the economic independence, as well as the costs to society because of the health and social care at work inform of absenteeism. However, despite this growing burden, there is a lack of priority on policies focusing in the area of musculoskeletal health.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report by WHO on analysis of Global Burden of Disease (GBD) 2019, data revealed that approximately 1.71 billion people globally live with musculoskeletal disorders, which include low back pain, neck pain, amputation (Cieza et al, 2020;Babantunde et al, 2022) Furthermore, this burden of disability as provided and estimated by the above summary on measures of health has an impact on the individual's quality of life, during and outside of their job, and the economic independence, as well as the costs to society because of the health and social care at work inform of absenteeism. However, despite this growing burden, there is a lack of priority on policies focusing in the area of musculoskeletal health.…”
Section: Introductionmentioning
confidence: 99%